DISKURSUS HAK ASASI MANUSIA DALAM AL-QUR’AN KARYA: ACHMAD ABU BAKAR: (Analisis Terhadap Suatu Kajian Tematik) - Sitti Musyahidah (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
The breakdown of the information about the existence of Human Right in Al-Quran along with its entity and nature comprehended by Achmad Abubakar is provided in this paper. The term of Human Rights is begun with the appellation of human existence itself in accordance with the emphasis of human as mustakhlaf Q.S. al-An’am (6) : 165 and as musta’mir (Q.S. Luqman [31] : 20). Allah has created the universe by means of inhabitants duty to prosper it by managing it. Hereinafter, human as basyar implies that they own rights. Thus, by apprehending human existence, an introduction of human dignity is then come out scilicet Human Rights’ entity - using ‘lam’ particle meaning entitlements. By utilizing those rights, it covers all rights owned by people as expressed in Al-Qur’an. Human Rights nature in Al-Qur’an is an explanation of Human Rights’ entity that are the presence of the right to life (Q.S. al-Maidah [5] : 32, the right to own (Q.S. Al-Jum’ah [62] : 10), and the right to believe (Q.S. [103] : 6).